Effect of Bee venom-Acupuncture Therapy on Patients with Sprain of the Wrist Joint - Byeong-Jun, An; Ho-Sueb, Song (Korean Pharmacopuncture Institute, 2006)
Objective : This study was to evaluate the effect of Bee venom-Acupuncture therapy on patients with sprain of the wrist. Methods : We investigated 31 cases of patients with sprain of the wrist. We flip a coin and divide patients into two groups. Bee venom-Acupuncture was performed at on group, and the other group we didn't do it. We evaluated the treatment effect of each group by using the visual analog scale(VAS). Results : 1. As a result of evaluation by using the VAS, the score after treatment was marked lower than that before treatment within each group. 2. After treatment, Bee venom-Acupuncture therapy group showed significant difference on visual analog scale(VAS) compared with acupuncture therapy group. Conclusion : These results suggested that Bee venom-Acupuncture treatment should be more effective in the patient with sprain of the Wrist joint.